Low-voltage bulk-driven flipped voltage follower-based transconductance amplifier - Durgam Rajesh; Subramanian Tamil; Nikhil Raj; Bharti Chourasia (Institute of Advanced Engineering and Science, 2022)
A low voltage high performance design of operational transconductance amplifier is proposed in this paper. The proposed architecture is based on bulk driven quasi-floating gate metal oxide semiconductor field effect transistor (MOSFET) which supports low voltage operation and improves the gain of the amplifier. Besides to this the tail current source requirement of operational transconductance amplifier (OTA) is removed by using the flipped voltage follower structure at the input pair along with bulk driven quasi-floating gate MOSFET. The proposed operational transconductance amplifier shows a five-fold increase in direct current (DC) gain and 3-fold increase in unity gain bandwidth when compared with its conventional bulk driven architecture. The metal oxide semiconductor (MOS) model used for amplifier design is of 0.18 um complementary metal oxide semiconductor (CMOS) technology at supply of 0.5 V.